Technological changes in the pulp and paper industry and the role of uniform versus selective environmental policy - Annegrete Bruvoll; Torstein Bye; Jan Larsson; Kjetil Telle (Statistics Norway, Research Department, 2003)
Although environmental regulations may imply a cost increase on firm's conventional input factors, such regulations could stimulate the incentives to improve factor productivity. Productivity measures including indicators capturing environmental improvements may also show higher or lower progress than productivity measures ignoring environmental aspects. We apply a Malmquist productivity index approach on micro data for the Norwegian pulp and paper industry, and find that the overall productivity growth accounting for changes in emissions of COD to water is higher than the growth in the productivity measure including conventional inputs only. We find the opposite result when including emissions of acids and climate gases to air. This is probably due to environmental regulations with opposing effects on different emissions. A decomposition of the Malmquist index into a technical efficiency change factor and a technical change component shows that the frontier technology has changed, while the average distance to the frontier has increased.
Keywords: L73; O12; O14; O33; O41; Q48; R38; 330; Emissions; Productivity change; Paper and pulp; Malmquist index; Frontier technology